Compare the Histological Features Between Normal and Hypertensive Placenta - Shahid Kamran, Tayyaba Kazmi, Nabeela Habib, Saleem Ahmed Bhutto, Muhammad Yousuf Khoso, Syed Irfan Raza Arif (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hypertensive disorders during pregnancy, including preeclampsia, significantly affect maternal and fetal health. Understanding the histological changes in the placenta under hypertensive conditions is essential to improving management and outcomes. This study aims to compare histological features in normal and hypertensive placentas. Objective: To assess and compare histological changes in placentas from patients with normal pregnancies and those with hypertensive disorders of pregnancy. Methods: A retrospective analysis of placental samples from 96 patients was conducted. The study included 48 normal pregnancies and 48 pregnancies complicated by hypertension. Histological features were examined, including villous architecture, vascular changes, fibrin deposition, and trophoblast morphology. Results: Significant differences were observed in the placental histology between normal and hypertensive pregnancies. In hypertensive placentas, abnormal spiral artery remodeling, villous fibrosis, increased syncytial knots, and fibrin deposition were prominent. In contrast, normal placentas exhibited well-formed villi with efficient blood flow and complete spiral artery remodeling. Conclusion: Hypertensive disorders lead to significant histological changes in the placenta, which may contribute to adverse maternal and fetal outcomes. Histological assessment can aid in understanding the pathophysiology of hypertensive pregnancies and improve clinical management. Keywords: Hypertensive disorders, preeclampsia, placenta, histology, spiral arteries, fibrin deposition.